A training programm to improve neuromuscular and performance indices in female high school basketball players - Noyes, F. R.; Barber-Westin, S. D.; Smith, S. T.; Campbell, T.; Garrison, T. T. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to determine if a sports-specific training program could improve neuromuscular and performance indices in female high school basketball players. We combined components from a published anterior cruciate ligament injury prevention program for jump and strength training with other exercises and drills to improve speed, agility, overall strength, and aerobic conditioning. We hypothesized that this sports-specific training program would lead to significant improvements in neuromuscular and performance indices in high school female basketball players. Fifty-seven female athletes aged 14-17 years participated in the supervised 6-week program, 3 d/wk for approximately 90-120 minutes per session. The program was conducted on the basketball court and in weight room facilities in high schools. The athletes underwent a video drop-jump test, multistage fitness test, vertical jump test, and an 18-m sprint test before and upon completion of the training program. All the subjects attended at least 14 training sessions. After training, a significant increase was found in the mean estimated VO2max (p < 0.001), with 89% of the athletes improving this score. In the drop-jump video test, significant increases were found in the mean absolute knee separation distance (p < 0.0001) and in the mean normalized knee separation distance (p < 0.0001), indicating a more neutral lower limb alignment on landing. A significant improvement was found in the vertical jump test (p < 0.0001); however, the effect size was small (0.09). No improvement was noted in the sprint test. This program significantly improved lower limb alignment on a drop-jump test and estimated maximal aerobic power and may be implemented preseason or off-season in high school female basketball players.